Transição agroecológica: um estudo de experiências no Brasil e no México - Corbari, Fábio (2020)
The present work deals with the study of the agroecological transition based on experiences in Brazil and Mexico. The objective was to identify agroecological transition experiences, analyzing them based on their stories, rupture and motivation processes, reproduction strategies, challenges faced and the contributions of these experiences to agroecological transition towards the construction of sustainable agrofood systems. We sought to establish relationships between the cases analyzed in the Paraná 3 Basin - BP3, located in the West of Paraná - Brazil, and in Mexico, located in the Texcoco de Mora region, Metropolitan Area of Mexico City. Common aspects, contrasts and complementations between them were analyzed. As a method of investigation, participatory action was used, requiring the involvement of the researcher as an agent in the process. Participatory methodological tools and procedures were used to gather information about the experiences and the context in which they are inserted. It was found that in BP3 the experiences of agroecological transition took place in the context of a large socio-environmental program, with the presence of agroecological rural extension, alternative food networks, participatory certification, cooperative solidarity, productive diversity of peasant properties and the presence of public policies, with emphasis on institutional market policies. Mexican experiences demonstrated the cultural roots of peasant practices, valuing traditional agroecosystems, promoting alternative food networks, bringing farmers and consumers closer to ecologized relationships, favoring healthy eating, fair trade and co-construction of knowledge. It is noteworthy that both in BP3 and in the Mexican region, the reproductive strategies of agroecological social actors promoted transformations based on experiences of resistance to hegemonic processes. It was concluded that the agroecological transition process occurs at several scales (from changes in agricultural practices in agroecosystems to the construction of new connections and food networks towards a sustainable global food system) and in a non-linear manner, with the participation of multiple social actors, acting in various dimensions of transition. The Latin transition experiences are complementary and point to a new project for agriculture and rural development, in tune with the agendas of sustainability and with the major trends and demands of society, moving towards a model that strives for the care of natural goods, for the concern with climate change, the maintenance of biodiversity and a more just and supportive society.